Determining the heat flow through the cabinet walls of household refrigerating appliances. (January 2021) - Paul, Andreas; Baumhögger, Elmar; Elsner, Andreas; Moczarski, Lukas; Reineke, Michael; Sonnenrein, Gerrit; Hueppe, Christian; Stamminger, Rainer; Hoelscher, Heike; Wagner, Hendrik; Gries, Ulrich; Freiberger, Alfred; et al.
Highlights: A measurement method for determining the k  ·  A value of household refrigerating appliances is presented. A latent heat sink is a suitable alternative to the reverse heat leak method. Air flow and storage temperatures in the refrigerator compartment are comparable to the real operating conditions. Temperature gradients between the storage room and the ambient of the refrigerating appliances are more realistic. An age-related increase of the k  ·  A value of between 3.6% and 11.5% was found over a period of 14 months. Abstract: The increase of the thermal conductivity of PUR foam in the insulation of the cabinet is an important cause for aging processes of household refrigerating appliances. To determine the influence of the PUR foam aging on energy consumption, the development of a new measurement method is necessary because current methods influence the aging behavior of household refrigerators and are therefore not applicable in general. Based on a latent heat sink, constructed as an ice water bucket, a new measurement method is developed to determine the k  ·  A value over time. With this method, the k  ·  A value of four household refrigerating appliances was determined over an interval of 14 months. The k  ·  A value increased between 3.6% and 11.5% during this period.